Review Artikel : Sediaan Steril Injeksi - Miya Hartini Nur Wakhid; Fina Nikmatul W; Windi Tri Wahyuni; Rizki Amalia Putri; Dewi Nur Halisa; Magdalena Kasih Belaon Lebuan; Dewi Rahmawati; Dzakiya Zhihrotulwida; M. Fithrul Mubarak (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Sterile injection preparations are liquid pharmaceutical preparations that are specifically designed to be administered directly into the body through injection using a sterile syringe or clean injection device. The main requirement for sterile injection preparations is that they must be free from microorganisms, foreign particles, and pyrogenic substances that can trigger fever or infection reactions in patients. Testing the quality of sterile injection preparations includes various aspects, ranging from sterility testing, pyrogenicity testing, clarity testing, to stability testing during the shelf life. Stability testing aims to ensure that the preparation remains safe, effective, and stable until its expiration date. The purpose of this study was to determine the evaluation of sterile injection preparations. The method used is by reviewing journals from Google Scholar, Pubmed, etc. from 2018-2024.